Repurposing content for online learning: a case study of the canadian open university / Stella Lee and Corinne Bosse - Lee, Stella; Bosse, Corinne (Penerbit UiTM (UiTM Press), 2009)
Following the adoption of new Strategic Plans, Athabasca University has been in the process of transforming its print-based courses to online content delivery for the past five years. This paper aims to report on the recent developments and issues on this transition, specifically, the steps and strategies the Educational Media Development team took to assess existing content and how to repurpose them for e-learning. Strategies such as how to adapt print production to online learning; the integration of various components of course websites; and the move towards integrating content into learning management system such as Moodle.